Dilute sulfuric acid hydrolysis of red macroalgae Eucheuma denticulatum with microwave-assisted heating for biochar production and sugar recovery. (December 2017) - Teh, Yong Yi; Lee, Keat Teong; Chen, Wei-Hsin; Lin, Shih-Cheng; Sheen, Herng-Kuang; Tan, Inn Shi
Graphical abstract: Highlights: A red macroalga E ucheuma denticulatum was used for biochar and reducing sugars production. Dilute sulphuric acid hydrolysis with microwave-assisted heating was performed. The calorific value of the biochar could be intensified by up to 45%. The highest total reducing sugars were 51.47 g/L (74.84% yield). The optimum conditions for the macroalga hydrolysis were at 160 °C with 0.1 M H2 SO4 . Abstract: This study aims to produce biochar and sugars from a macroalga Eucheuma denticulatum using dilute sulfuric acid hydrolysis along with microwave-assisted heating. The reactions were operated at sulfuric acid concentrations of 0.1 and 0.2 M, reaction temperatures of 150–170 °C and a heating time of 10 min. Compared to the raw macroalga, biochar qualities were improved with increased carbon content and lower ash and moisture contents. The calorific value of the biochar could be intensified up to 45%, and 39% of energy yield was recovered. Apart from producing biochar, the highest total reducing sugars were 51.47 g/L (74.84% yield) along with a low by-product 5-HMF of 0.20 g/L, when the biomass was treated under the optimum conditions at 160 °C with 0.1 M H2 SO4 . Thus, this study demonstrated that macroalgae could be potentially used as biomass feedstock under microwave-assisted acid hydrolysis for the production of biofuel and value-added products.